Pengetahuan dan Keterampilan Artikulasi Hak Kesehatan Seksual dan Reproduksi (HKSR) di Kalangan Perempuan Muda Asli Papua - Desintha Dwi Asriani; Godefridus Samderubun; Eling Wening Pangestu (Jurnal Perempuan, 2023)
This article discusses the extent to which the SRHR narrative is reproduced in the Papuan context. In the process, data collection was carried out by combining document studies, self-reflexive, and interviews. The involvement of one of the researchers who is also an Indigenous Papuan (Orang Asli Papua – OAP) allows for self-reflection regarding the context and issues of SRHR in Papua. While in the interview process, women’s bodily experience is placed as a center for understanding the dynamics of reproductive health problems in the broader context of Papua. Specific issues such as unwanted pregnancies (Kehamilan Tidak Diinginkan – KTD) are key topics during the interview process. The results of the study show that SRHR issues among young people in Papua cover specific issues such as unwanted pregnancy, HIV/AIDS, and violence against women. However, in the exploration of specific topics such as KTD, it was found that there is a gap in knowledge and skills in understanding and translating the substance of SRHR due to conflicting economic issues, traditions, and changes in meaning around sexuality due to the influence of modernization. Therefore, the intersectionality framework, both theoretically and methodologically, has the potential to be developed for further studies to obtain a comprehensive mapping of the dynamics of SRHR challenges and the need for innovative approaches in Papua.